The Future of Farmer organisations: Opportunities and Challenges in Achieving Household Food Security. Evidence from Acholi Subregion, Northern Uganda - Margaret, Namubiru; Kijjambu, Frederick Nsambu; Rwakihembo, John (Journal of Developing Economies, 2022)
Purpose: The study set out to determine the relationship status of farmers’ organisations in the region, examine the opportunities for farmer organisations in achieving households’ food security, and investigate the challenges farmer organisations face in achieving household food security. Methodology: The study used descriptive, correlational and cross-sectional research designs grounded by a mixed-methods approach. Quantitative data was collected on a sample of 370 households using a structured questionnaire, while qualitative data was collected from 16 face-to-face interviews. The study used both purposive and simple random sampling techniques. Data analysis was done using descriptive and Pearson correlation analyses, while thematic content analysis generated qualitative results. Findings: The Study indicated a positive albeit weak relationship between farmer organisations and household food security in the Acholi Sub-region. The results indicated that most farmer organisations are inactive and informal with low household participation. A possible explanation could be the small membership size and organisations’ inability to tap existing production and marketing opportunities. Unique contribution to practice and policy: The study guides the government in creating an enabling environment that supports farmer organisations in accessing external markets and market information by improving infrastructure and strengthening capacity building of farmer organisations to increase food security.
Keywords: Farmer Organization; Household; Food Security